Pengaruh Pekerjaan terhadap Kemampuan Menyeimbangkan Kuliah dan Pekerjaan pada Mahasiswa Universitas Pembangunan Panca Budi - Mouza Hasanah; Citra Yasmin; Dewi Jelita; Jauzaa Fadhiilah; Innaya Lutfiah Salsabila; Ikhah Malikhah (Universitas Nusantara PGRI Kediri, 2026)
This study aims to determine the impact of work on the ability of students at Panca Budi Development University (UPP) to balance study and work. Qualitative methods were used through interviews with 10 students who work while studying. The results indicate that the students' primary motivations are to ease their family's financial burden and gain work experience. Students who have good time management skills and receive support from their campus and workplace are better able to maintain a balance between study and work.